Public Responses to Religious Issues in the Media: A Case Study of the Viral News of Kyai Lirboyo in 2025 - Khonsa Miftahurrohmah (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2026)
Religious intolerance has colored religious discourse in Indonesia in recent years. Religious intolerance includes things such as bans on the construction of houses of worship, bans on book debates, attacks on certain organizations, accusations of heresy against certain religious groups, threats of hate speech. The main method used in this study uses the study research method to analyze the dynamics of religious tolerance issues in the public sphere amidst societal polarization. The purpose of this study is to determine how quickly the impact and public response to religious issues. The results of the discussion conclude that the public response to religious issues in the media: a study of the case of the viral news of Kyai Lirboyo in 2025 is very fast. The students and Kyai immediately gave criticism and the hashtag #boycottTrans7 after the video broadcast by "Xpose Uncensored" on Trans7.